'Be an optimizer!': The lesson of the 'inconclusive' trial for aggressive behavior. Issue 9 (17th August 2021) - Knopf, Alison
Abstract : In the editorial, "Why JAACAP Published an 'Inconclusive' Trial: Optimize, Optimize, Optimize Psychostimulant Treatment, " Samuele Cortese, M.D., Ph.D., and Douglas K. Novins, M.D., write about the results of the double‐blind randomized controlled trial (RCT) aimed at assessing the comparative efficacy and tolerability of adjunctive risperidone, divalproex sodium, or placebo for aggressive behaviors in children with attention‐deficit hyperactivity disorder (ADHD) and comorbid oppositional defiant disorder or conduct disorder, as well as a prior history of psychostimulant treatment (see story, page 1).